Basic studies in biaxial tensile tests. Issue 1 (9th May 2018) - Hartmann, Stefan; Gilbert, Rose Rogin; Sguazzo, Carmen
Abstract : Biaxial tensile experiments are an increasing test alternative of thin‐walled specimens to characterize the material behavior under mechanical agencies. This is mainly driven by digital image correlation systems to obtain information about the surface deformation. However, it is not as simple as a tensile test since we can only measure the deformation in a region on the specimen and not the stress state. The latter aspect of stress determination is discussed as well. In this article, we address several basic questions. First: can we obtain a homogenous strain state in cruciform‐like specimens? In this sense the shape will be discussed and a measure of homogeneity is introduced for proofing whether homogeneity can be guaranteed. Second: how can we reach large strains in the center of the specimens? This is connected to the specimen's geometry (arm reinforcement, slots, thinning of center, …). Furthermore, we discuss the problem of material parameter identification using biaxial tensile test information, which is connected to the concept of identifiability using finite elements. This is discussed at the simplest constitutive model, namely linear isotropic elasticity. Thus, the overall goal is connected to a critical review on biaxial experiments using cruciform specimens. The test materials are polymers.